Core principles of soil mechanics - Shukla, Sanjay Kumar (ICE textbooks, 2014)
ICE Textbooks provide clear, accurate and relevant information on the major principles of civil and structural engineering at a level suitable for undergraduate students worldwide. Divided into easily understandable modules, ICE Textbooks feature worked examples, practice questions and learning point summaries throughout. This textbook covers the concepts of major topics in soil mechanics through a simple, practical approach for easy learning within in a limited timeframe. Covering the principles and recent developments of topics such as soil classification and characteristics, consolidation and compressibility, shear strength, stresses and fluid flow, the book is extensively illustrated, including worked examples throughout and a summary of key learning points at the end of each chapter as well as self-assessment question and answer sections.